Integrating Project Citizen and Qanun Jinayat in Civic Education to Prevent Sexual Violence in Acehnese Higher Education - Helminsyah, Helminsyah; Yusnadi, Yusnadi; Surya, Edy; Kasmini, Lili; Mulyani, Mulyani (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This study aims at investigating the university students’ perceptions of the Project Citizen learning model on civic education with the integration of the local wisdom, Qanun Jinayat, to prevent sexual violence. This study employed a mixed-method which gathered data using questionnaires and interviews. The participants involved in this study were 68 students for questionnaires and 7 students for the interviews from Universitas Bina Bangsa Getsempena Banda Aceh, Aceh, Indonesia. Quantitative data were analyzed descriptively, while qualitative data were analyzed thematically. The findings of study reveal that students generally held positive views on integrating Qanun Jinayat through Project Citizen to protecting against sexual violence. Students also recognized Qanun Jinayat as a culturally and legally legitimate framework and valued its integration into participatory, problem-based learning. They also identified challenges such as stigma, fear, and institutional gaps, while putting emphasis on the importance of community collaboration and their own active roles in the prevention of sexual violence. Thus, universities are encouraged to integrate local wisdom and legal literacy into their curricula and to strengthen collaboration with community and legal institutions to prevent sexual violence.